A quality control study on Pure Foods Corporation - Ben, Rolly D.; Catillo, Dominador III; Mancenido, Michelle V.; Omictin, Michael Philip (College of Engineering, 2002)
Purefoods Corporation bears the reputation of being country's leading manufacturer of the Chicken Nuggets,snack-sized emulsified chicken patties coated with golden-brown breading.Recent buy-out negotiations between San Miguel Corporation and the Ayala Group Companies paved the way for the augmentation of Chicken Nuggets production.One site catering to Chicken Nuggets production is the Agro foods Processing Plant in Balagtas,Bulacan, a few kilometers away from the central town Malolos.The 5-year production contract between Purefoods and Agro Foods embarked in the year 2000.The terms are simple,Purefoods provides the raw materials needed for production the raw materials needed for production,Agro foods turn the raw materials into finished products sealed in PE bags, and Purefoods buys back the recovered weight as toll pay.Such that, for a recovered weight less than 5000 kilos,Purefoods pays P22 per kilogram.The greater the recovered weight,the lesser that Purefood pay P22 per kilogram.Agro Food is allowed a maximum of 2-3% rejection rate per week.In the case that the rejection rate exceeds the defined,Agro is compelled to buy the excess weight for the market price of 49.75%/230 grams.By analyzing the data for one normal production month,the study has inferred that the average rejection per rate per week is 2%.Projected over 12 months,a 2%rejection rate amounts to nearly P1.5 million in raw material and opportunity losses,amount that the team believes might be invested in significant quality improvement activities.Moreover,since it has been disclosed by Purefoods' management that a 0% rejection rate is not feasible due to inherent flaws in the system,a 0.5% rejection rate is used to calculate for the incremental decrease in opportunity losses if the rejection rate decreases to the mentioned percentage.The finding signified a 75% decrease in opportunity losses.There are three main causes for rejection:off-shape,wrong color,and presence of glands (due to insufficient mixing).Throgh Pareto Analysis,two are determined to occur most frequently:the problem of off:shape and wrong color.The root causes for both factors are enumerated and categorized (MAN,METHODS,MACHINE,MATERIALS,MANAGEMENT)by consulting with the management staff,and directly observing several production runs.Statistical Process Control and Process Capability Analysis is were used to analyze each production process(forming,breading,battering,and frying)for capability and stability.Most processes were found to be both unstable and incapable (with the exception of battering,which is capable but unstable).Process instablity and incapability increases the probability of producing end-products which do not conform to specifications (both variable and attribute).It also increases the chances of reworking,which might be a potential cause of microbial growth.The control were used to verify of the root causes for rejection,which are the following:Faulty oven thermostat,Auger deterioration,Defective hydraulic pump,Excessive raw material transport.Unfortunately,relationship between factors in the production line could not be verified.For instance,the direct effects of conveyor speed to the completed of breading could not be inferred,due to lack of data.Because of this, a Design of experiment is recommended to find out and input parameters affecting the desired output.The sampling system of Purefoods for its chicken nugget line was found to have a high consumer's risk.As an example,sampling for finished goods takes 1 sample out of one entire lot,which has about 450 packs of chicken nuggets.At the current system,if there are 30% defective packs,there is still a 90% probability that the lot will be accepted.The implementation strategy of the recommended are divided among 5 phases.Phase 1:Design of Experiment,Phase 2: process improvements,Phase 3: SPC Installation,Phase 4: Sampling System Improvement,Phase 5:Evaluation and Standardization.Each phase is discussed in detail.Since most of the alternatives under Phase 2 could not be evaluated for cost and benefits,a separate section called AREAS FOR FURTHER STUDY, was included to list some area of concern that might instigate interest and future study and research.